Alternative in anxious and fearful times: sensitive listening for healthy writing - Moura, Carla (Farol, 2024)
Contemporary society seems to be immersed in an unprecedented state of fear, anxiety and distraction. In this context, professionals and students, whose writing is more relevant, increase focus and reduce tension demonstrate additional challenges. The main objective of this text is to offer teaching techniques that contribute to the development of sensitive listening for healthy writing. Resulting in greater self-awareness, health promotion and professional and relational benefits.